A flange-type standard leak element and its vacuum applications. (February 2021) - Chan, C.K.; Yeh, S.D.; Chang, C.C.; Tu, C.Y.; Yang, I.C.; Chang, K.L.; Luo, C.W.; Hwang, C.S.
Abstract: A previous article [C.K. Chan et al., Vacuum 180, 109650 (2020)] described a gasket-type standard leak element (SLE) that could be employed to solve the problem of serious outgassing and the constraint of a low baking temperature (<120 °C) caused by the use of an epoxy resin sealant (Torr Seal®) on a sealing interface. Here, we propose a leak element of a new type using femtosecond laser micromachining to drill a microscale channel on a double-sided ConFlat (CF) flange. Not only is the flange-type SLE reusable but also its performance is as effective as that of a gasket-type SLE. This useful device can be widely applied to many vacuum technologies and applications, which are also described in this paper. Highlights: A demountable and reusable flange-type standard leak element with a microfluidic channel was developed. This SLE could be employed to overcome the issues related to the use of an epoxy resin sealant in SLE of other types. This device can be widely applied to many vacuum applications, such as gauge calibration and measurement of pumping speeds.